Do Preoperative Epidural Steroid Injections Increase the Risk of Infection After Lumbar Spine Surgery?. Issue 3 (1st February 2021) - Kreitz, Tyler M.; Mangan, John; Schroeder, Gregory D.; Kepler, Christopher K.; Kurd, Mark F.; Radcliff, Kris E.; Woods, Barrett I.; Rihn, Jeffery A.; Anderson, D. Greg; Vaccaro, Alexander R.; Hilibrand, Alan S.
Abstract : Study Design: Retrospective study. Objective: To elucidate an association between preoperative lumbar epidural corticosteroid injections (ESI) and infection after lumbar spine surgery. Summary of Background Data: ESI may provide diagnostic and therapeutic benefit; however, concern exists regarding whether preoperative ESI may increase risk of postoperative infection. Methods: Patients who underwent lumbar decompression alone or fusion procedures for radiculopathy or stenosis between 2000 and 2017 with 90 days follow-up were identified by ICD/CPT codes. Each cohort was categorized as no preoperative ESI, less than 30 days, 30 to 90 days, and greater than 90 days before surgery. The primary outcome measure was postoperative infection requiring reoperation within 90 days of index procedure. Demographic information including age, sex, body mass index (BMI), Charlson Comorbidity Index (CCI) was determined. Comparison and regression analysis was performed to determine an association between preoperative ESI exposure, demographics/comorbidities, and postoperative infection. Results: A total of 15, 011 patients were included, 5108 underwent fusion and 9903 decompression only. The infection rate was 1.95% and 0.98%, among fusion and decompression patients, respectively. There was no association between infection and preoperative ESI exposure at any time point (1.0%, P = 0.853), ESI within 30 days (1.37%, P = 0.367), ESI within 30 to 90 days (0.63%, P = 0.257), or ESI > 90 days (1.3%, P = 0.277) before decompression surgery. There was increased risk of infection in those patients undergoing preoperative ESI before fusion compared to those without (2.68% vs . 1.69%, P = 0.025). There was also increased risk of infection with an ESI within 30 days of surgery (5.74%, P = 0.005) and when given > 90 days (2.9%, P = 0.022) before surgery. Regression analysis of all patients demonstrated that fusion ( P < 0.001), BMI ( P < 0.001), and CCI ( P = 0.019) were independent predictors of postoperative infection, while age, sex, and preoperative ESI exposure were not. Conclusion: An increased risk of infection was found in patients with preoperative ESI undergoing fusion procedures, but no increased risk with decompression only. Fusion, BMI, and CCI were predictors of postoperative infection. Level of Evidence: 3 Abstract : A retrospective study was conducted to elucidate any possible association between preoperative ESI and postoperative infection in a large population of patients undergoing lumbar spine surgery. Patients undergoing lumbar fusion surgery had an increased risk of postoperative infection with preoperative ESI. Fusion, BMI, and CCI were independent predictors of infection.